Determination of standard reference renal volume model and dose optimisation procedures for clinical applications - Shirazu, Issahaku (University of Cape Coast, 2018)
The study is based on measurements of renal dimensions and related body indices to establish standard reference body and renal parameters, renal volume model, renal and effective dose in relation to patients’ dose optimization procedures. The materials used include: MDCT Machine, Weighing scale, BMI calculator and MVL workstation. Technical parameters were obtained from three groups of randomly selected patients undergoing abdominal CT examinations including: 175 patients of age 20-40 years, 258 patients of age 41- 60 years and 227 patients of age 61-80 years. In addition, the models design were based on age and gender variations. Voxel count method was used as the measuring tools with an integrated MVL application software platform, together with Minitab 16 statistical tools. The average values of the measured parameters include: the renal volumes: 146.74 cm3 , 151.76 cm3 , 142.04 cm3 , 148.29 cm3 for male and female, with each corresponding right and left kidneys, respectively: renal length: 103.35 cm, 105.13 cm, 101.43 cm and 102.98 cm for male and female with the corresponding right and left kidneys respectively, the estimated renal volumetric ellipsoid coefficient (K) and renal shape index for both gender were approximately 0.53±0.01 and 1.00±0.02 respectively. The mean BMI, BSI and BSA were: 25.19 kg/m2 , 39.81 kg/m2 and 2.02 m2 for male and 21.91 kg/m2 , 36.58 kg/m2 and 1.69 m2 for female respectively. In addition, the mean dose parameters were: 6.33 mGy, 936.25 mGy cm, 3.26 mSv and 14.09 mSv for CTDIV, DLP, RD and E respectively. Two Comprehensive Clinical Decision Support Application Software were designed to provide a user friendly platform for comfortable working process. Finally, the established reference parameters are recommended for clinical application
xviii,222p;,ill
Keywords: Effective Dose MeVisLab Minitab Optimization Renal Dose Voxel.